Role of Mechanical Loading for Platelet-Rich Plasma-Treated Achilles Tendinopathy. Issue 6 (June 2020) - Neph, Alyssa; Schroeder, Allison; Enseki, Keelen R.; Everts, Peter A.; Wang, James H-C.; Onishi, Kentaro
Abstract : Abstract: There is no consensus on the optimal rehabilitation protocol after platelet-rich plasma (PRP) treatment for tendinopathy despite basic science studies showing the critical role of mechanical loading in the restoration of tendon structure and function posttreatment. In this article, we will review tendon mechanobiology, platelet biology, and review levels I and II Achilles tendon clinical studies paying particular attention to the role of mechanical loading in rehabilitation of injured tendons. Animal studies emphasize the synergistic effect of mechanical tendon loading and PRP to treat tendon injury while clinical studies described minimal details on loading protocols.